Association of hypertensive disorders of pregnancy with offspring cardiometabolic indicators: a systematic review and meta-analysis - Xu, Hong; Liang, Yujie; Li, Peishan (Frontiers in Endocrinology, 2025)
BackgroundHypertensive disorders of pregnancy (HDP) are a major public health problem affecting a large number of pregnancies worldwide. Despite extensive research, little is known about the long-term cardiometabolic consequences of HDP exposure in offspring.ObjectiveTo investigate the long-term cardiometabolic risks in offspring exposed to HDP.Search strategyA comprehensive search of relevant studies published in PubMed, EMBASE, the Cochrane Central Register, and Web of Science databases was conducted.Selection criteriaInclusion criteria comprised case-control and cohort studies, with outcome measures encompassing blood pressure, body mass index, lipid levels, and glucose metabolism.Data collection and analysisMeta-analysis was performed using Review Manager 5.4, and fixed- or random-effects models were selected as appropriate.Main resultsA total of 23 observational studies with 89,982 participants from 10 countries were included. Meta-analysis indicated that offspring exposed to HDP presented with significantly increased systolic blood pressure (MD: 2.44; 95% CI: 2.03–2.85; P < 0.00001), elevated diastolic blood pressure (SMD: 0.19; 95% CI: 0.15–0.23; P < 0.00001), and higher body mass index (MD: 0.34; 95% CI: 0.05–0.64; P < 0.05). Additionally, these offspring demonstrated a decreased likelihood of elevated homeostasis model assessment of insulin resistance (OR: 0.58; 95% CI: 0.34–0.98; P < 0.05). No significant differences were observed in other indicators.ConclusionsThe impact of HDP on offspring cardiometabolism is multifaceted. Elevated blood pressure and body mass index are more likely to be observed in offspring exposed to HDP, while the risk of insulin resistance appears to be reduced.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025630378, identifier CRD42025630378.